Rate of transmission and endogenous origin of Candida albicans and Candida glabrata on adult intensive care units studied by pulsed field gel electrophoresis - Hamal, P; Kappe, R; Rimek, D (The Journal of hospital infection, 2001)
We determined the relative roles of endogenous origin and patient-to-patient transmission in Candida colonization of patients on adult intensive care units (ICU). A total of 48 Candida albicans and 18 Candida glabrata strains from various clinical samples of 28 long-term patients, hospitalized in two neurological ICUs between April and June 1999, were typed using pulsed field gel electrophoresis (PFGE). Three patients were co-colonized by both C. albicans and C. glabrata strains. Twenty-four C. albicans and 17 C. glabrata karyotypes were defined. The colonization was found to be polyclonal in six C. albicans and five C. glabrata patients. Twenty-six patients (93%) carried strains, which were not detected in other patients hospitalized at the same time, i.e. they were colonized by unique C. albicans and C. glabrata strains. Only two patients, who were hospitalized during the same period of time, although in different rooms of the same ICU, shared strains with an identical PFGE type, indicating possible patient-to-patient transmission. Patient-to-patient transmission of yeasts played a minor role on these ICUs.
Keywords: Mycological Typing Techniques; dospělí; jednotky intenzivní péče; Candidiasis; pulzní gelová elektroforéza; Germany; Female; Adult; ženské pohlaví; Adolescent; lidé; Německo; Electrophoresis, Gel, Pulsed-Field; Cross Infection; mykologické určovací techniky; Intensive Care Units; retrospektivní studie; Male; Aged; infekce spojené se zdravotní péčí; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; kandidóza; Humans